Endorse Pakaian Wanita pada Kaum Pria (Tasyabbuh) dalam Tinjauan Etika Bisnis Islam (Studi Kasus Selebgram Pria di Kota Pontianak) - Saragih, Eka Junila; Abdurrahman, Abdurrahman (Sharia Faculty Islamic Economic Law Study Department, 2022)
This study examines the endorsement of women's clothing used by men. Business actors in marketing their products use endorsement services. This phenomenon is what happened in Pontianak city; found male endorsers received endorsements such as the use of wigs, makeup, and women's clothing that women should use. This research uses an empirical method that is descriptive with a qualitative approach. The primary data source in this study is a Celebrity Endorser Instagram (Celebgram) in Pontianak city. At the same time, secondary data are obtained from related books and documents. The deeds done by the endorser are deeds that simulate women and in Islam are called tasyabbuh. Tasyabbuh is clearly forbidden in Islam. Tasyabbuh did by a man to a woman concerning the endorsement activity, and if it connected to the fiqh law rules is returned to the endorser intension. All acts committed by a person are penalized according to what he intends, including those done by the endorser. The phenomenon seen here is that these endorsers try to look as similar as possible to women and show femininity lying in the form of tasyabbuh.